Prevention of mother-to-child transmission of HIV service interruptions amid COVID-19 pandemic - Florence M.Q. Setshedi; Livhuwani Tshivhase; Idah Moyo (South African Family Practice)
Background: The coronavirus disease 2019 (COVID-19) caused global disruptions in healthcare service delivery. The prevention of mother-to-child transmission (PMTCT) of human immunodeficiency viruses (HIV) services were also interrupted, threatening the attainment of Sustainable Development Goal 3. This article describes the PMTCT service interruptions experienced during the COVID-19 pandemic in Tshwane healthcare facilities.